Personality and Interpersonal Communication - Drew, Savanha; Benson, Brooke; Goodman, Jeffrey A. (My University, 2017)
The purpose of this study was to determine if individuals raised in specific regions of the United States differ in their propensity to avoid interpersonal conflict. Regions of the United States are known to differ in Big Five Personality Inventory scores such that Friendly and Conventional; Relaxed and Creative; and Temperamental and Uninhibited regions have been identified. Participants took a Qualtrics survey that included the Big Five Personality Inventory, the Conflict Communication Scale, the Harmony Scale, a Political Ideology Questionnaire, and demographic background questions. Participants were placed into a US geographical region based on where they grew up and a personality profile based on their Big Five scores. Subsequently, geographic region and personality profile were treated as quasi-independent variables. We hypothesized that individuals born and raised in the Midwest, or the Friendly and Conventional region of the United States, avoid interpersonal conflict to a greater degree than those born and raised in the Temperamental and Uninhibited Region of the United States. Our findings will contribute to research on connections between personality and behavior and to our understanding of US regional cultural differences.
Color poster with text and diagrams.
Keywords: Personality traits; Regional Differences; Interpersonal communication; Posters